energy transition in Europe XVII- XX century. - Madureira, Nuno Luis (V MEETING OF REPORT(H)A PORTUGUESE NETWORK OF ENVIRONMENTAL HISTORY, 2023)
This presentyation explains the diversity in energy transitions taking place in Europe between the eighteenth and twenty-first centuries. This thus demonstrates how Europe experienced two different transitions from the epoch-long solar energy regime to the coal based regime. This also points out how the transition towards oil and natural gas differed completely from the previous transition to coal because it was swifter, overwhelming and led by a different group of nations. After World War II, the European split between a capitalist West and a communist East also imparted a division between oil and coal economies. What we may expect from the current transition to renewable energy accounts for the chapter's closing theme